Pendidikan Anak dalam Psikologi Pendidikan Islam: Kajian Konseptual dan Teoritis - Priyanto Priyanto; Siti Rohimah (Lembaga Yasin AlSys, 2026)
Child education from the perspective of Islamic educational psychology is a holistic process that is oriented not only toward the development of cognitive aspects but also toward the comprehensive formation of children’s character, moral, spiritual, emotional, and social dimensions. This study aims to analyze the concept of child education in Islamic educational psychology, identify factors that influence children’s development, examine effective educational methods, and explore the challenges of its implementation in the modern era. This study used a literature study or library research method with a descriptive-analytical approach through the examination of various relevant primary and secondary sources. The data were analyzed using content analysis through the processes of identifying, classifying, synthesizing, and drawing conclusions from various literature findings. The results of the study show that child education in Islam places the values of monotheism, moral character, compassion, and balance between spiritual and intellectual aspects as the main foundation of education. Children’s development is influenced by family, school, and social environmental factors that play a role in shaping character and social skills. Effective educational methods include a holistic approach, active learning, role modeling, and the integration of Islamic values throughout the educational process. On the other hand, technological development and globalization are challenges that require adaptive strategies through collaboration among families, schools, and communities. The conclusion of this study affirms that Islamic educational psychology provides a comprehensive educational framework for shaping children who are intelligent, noble in character, spiritually mature, and able to face the dynamics of modern life.